2021
DOI: 10.1371/journal.pone.0246643
|View full text |Cite
|
Sign up to set email alerts
|

Fetal, neonatal, and infant outcomes associated with maternal Zika virus infection during pregnancy: A systematic review and meta-analysis

Abstract: The occurrence of fetal and neonatal disorders in pregnant women with Zika virus infection in the literature is not consistent. This study aims to estimate the prevalence rate of these disorders in fetuses/neonates of pregnant women with confirmed or probable infection by Zika virus. A systematic review with meta-analysis was conducted in November 2020. Cohort studies that contained primary data on the prevalence of unfavorable outcomes in fetuses or neonates of women with confirmed or probable Zika virus infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 72 publications
1
25
0
3
Order By: Relevance
“…Among other health care interventions, the connection between ‘prenatal care’ and m-ZIKV + was the strongest, possibly due to increases in health care once developmental problems in the fetus are identified [ 40 ]. For this factor, pcor 2 values successively decreased in the m-ZIKV − subnetwork to the LBW subnetwork and then to the B subnetwork.…”
Section: Resultsmentioning
confidence: 99%
“…Among other health care interventions, the connection between ‘prenatal care’ and m-ZIKV + was the strongest, possibly due to increases in health care once developmental problems in the fetus are identified [ 40 ]. For this factor, pcor 2 values successively decreased in the m-ZIKV − subnetwork to the LBW subnetwork and then to the B subnetwork.…”
Section: Resultsmentioning
confidence: 99%
“…28 But, maternal ZIKV infection has been associated with several serious fetal and neonatal defects including intracranial calcifications, ventriculomegaly, microcephaly, ocular abnormalities, fetal loss, small for gestational age, low birth weight, and prematurity. 9,28,29 Though several cognitive, sensory, and motor disabilities caused by ZIKV are also seen with other congenital infections, a unique congenital Zika syndrome has been described that includes five features: severe microcephaly, thin cerebral cortices with subcortical calcifications, macular scarring, congenital contractures, and extrapyramidal symptoms with hypertonia. 30 This is probably the first study from India studying the three arboviruses, that is, dengue, chikungunya, and Zika viruses in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The causal connection between ZIKV infection during pregnancy and subsequent birth defects, which are collectively referred to as Congenital Zika Syndrome (CZS), was confirmed with the detection of ZIKV RNA in amniotic fluid of pregnant women carrying children with microcephaly and the isolation of ZIKV from the brain of an infant who died after birth (6,8). Notably, multiple systematic reviews and meta-analyses performed after the end of the epidemic confirmed the association between ZIKV infection during pregnancy and CZS (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 87%